2020
DOI: 10.1002/dep2.122
|View full text |Cite
|
Sign up to set email alerts
|

Morphotype differentiation in the Great Barrier Reef Halimeda bioherm carbonate factory: Internal architecture and surface geomorphometrics

Abstract: The calcareous Halimeda bioherms of the northern Great Barrier Reef, Australia are the largest actively accumulating Halimeda deposits worldwide. They contribute a substantial component of the Great Barrier Reef neritic carbonate factory, as well as the geomorphological development of Australia's northeast continental shelf.Halimeda bioherm geomorphology is complex, expressing three distinct variations in morphotype patterns: annulate, reticulate and undulate. Similar regular and irregular geomorphological pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 74 publications
0
10
0
Order By: Relevance
“…Halimeda bioherms are a significant component of the region’s postglacial carbonate budget. A comparison of the most up-to-date morphometric data 27 shows that the postglacial Halimeda deposits are equivalent in mass to 5.5–10.5% of the Holocene reef mass on the GBR shelf (Table 1 ). Halimeda can form mounds in inter-reef areas of the GBR up to a thickness of 20 m 25 27 , 59 , 60 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Halimeda bioherms are a significant component of the region’s postglacial carbonate budget. A comparison of the most up-to-date morphometric data 27 shows that the postglacial Halimeda deposits are equivalent in mass to 5.5–10.5% of the Holocene reef mass on the GBR shelf (Table 1 ). Halimeda can form mounds in inter-reef areas of the GBR up to a thickness of 20 m 25 27 , 59 , 60 .…”
Section: Resultsmentioning
confidence: 99%
“…A comparison of the most up-to-date morphometric data 27 shows that the postglacial Halimeda deposits are equivalent in mass to 5.5–10.5% of the Holocene reef mass on the GBR shelf (Table 1 ). Halimeda can form mounds in inter-reef areas of the GBR up to a thickness of 20 m 25 27 , 59 , 60 . Recent reviews of published and new high-resolution bathymetry have revealed that at least 6000 km 2 of the northern and central GBR are covered by Halimeda bioherms 26 , 27 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The BTM is a pixel-based surface tool that allows the user to interrogate bathymetric data, on a pixel-topixel comparison (Walbridge et al, 2018). This tool is useful for identifying surface variation, characterizing and identifying seafloor morphology (Verfaillie et al, 2006;Rengstorf et al, 2012;Ismail et al, 2015;Watson et al, 2017;McNeil et al, 2020). This method provides a quantitative measure of seafloor variation, removing interpretation bias.…”
Section: Seafloor Classificationmentioning
confidence: 99%